EMPOWERING GLOBAL COMPETENCE THROUGH ENGLISH EDUCATION: A STRATEGIC POLICY APPROACH IN DEVELOPING COUNTRIES - Ergasheva Ozodabonu Bahodirjon qizi (INTEGRATION OF EDUCATION AND SCIENCE: GLOBAL CHALLENGES AND SOLUTIONS, 2025)
Abstract: In an increasingly interconnected world, global competence has become a crucial skill for the 21st-century workforce. English, as a global lingua franca, plays a pivotal role in enabling individuals to participate in international dialogue, access global knowledge, and compete in the global job market. This paper investigates how developing countries can strategically use English education to build global competence among students. The study emphasizes policy-level approaches that ensure equitable access, curriculum alignment, teacher training, and technological integration. Findings reveal that a well-designed national English education strategy significantly enhances students' ability to engage globally and contribute to sustainable development.